Displaced belongings: indigenous identity, customary law and the struggles for recognition in post-colonial migration systems - Chawaremera, Melisa M. (Frontiers in Human Dynamics, 2025)
This study critically explores the concept of displaced belongings in the context of post-colonial Southern Africa. It focuses on the systemic exclusion of indigenous and traditionally mobile communities. This is with particular reference to the legal and political frameworks of recognition of the Khoisan, San, Tsonga and Venda peoples. The imposition of arbitrary colonial borders, coupled with the dominance of Western legal systems, has undermined customary law and erased indigenous identity markers. As a result, these communities often face legal precarity, erasure and limited access to rights and services. Utilising a doctrinal and socio-legal review, this study examines how post-independence citizenship regimes have failed to address the border induced fragmentation of indigenous belonging. The study traces how the colonial carving of territories disrupted cross-border kinship and spatial arrangements and how this left many communities marginalised in the very regions that they historically inhabited. The study also assesses the extent to which international legal instruments such as the United Nations Declaration on the Rights of Indigenous Peoples and the ILO Convention No. 169 offer frameworks for redress and recognition. The research advocates for a reimagining of citizenship that accommodates plural legal traditions, honours indigenous identities and responds to the unique forms of displacement that is experienced by cross border communities in Southern Africa.